PENGARUH MENTAL SKILLS TRAINING TERHADAP TINGKAT KECEMASAN SEBELUM BERTANDING PADA ATLET PENCAK SILAT TAPAK SUCI MAN 3 KUNINGAN - Sandy Rizkya; Ribut Wahidi (STKIP Subang, 2026)
This study aimed to determine the effect of Mental Skills Training on pre-competition anxiety among Pencak Silat athletes of Tapak Suci MAN 3 Kuningan. This study used a quantitative method with a one-group pretest-posttest design. The participants were 10 athletes. The mental training consisted of breathing relaxation, imagery training, and self-talk for three weeks. Anxiety levels were measured using the CSAI-2R and analyzed using a paired sample t-test. The results showed that the athletes' average anxiety score decreased from 37.00 before the training to 26.40 after the training. The test result showed a significance value of 0.000 < 0.05, indicating a significant effect of Mental Skills Training on reducing pre-competition anxiety